AN INVESTIGATION OF MOOD AND TRANSITIVITY ANALYSIS IN THE SHORT STORY “FRUIT PASSION” - Haryani Haryani; Ainur Rosyidah Azmie Putry (Universitas 17 Agustus 1945 Semarang, 2020)
This research aimed to investigate mood and transitivity analysis employed in popular short story Fruit Passion. the reseacher choose one of short story from 8th grade of junior high school students’ textbook. This text belongs to jokes for kids which mostly found in meme. The objectives of the research are analysing the interpersonal meaning realized in the short story by identifying the mood types, speech roles, and modality. Besides that, identifying the process based on ideational meaning and explaining the contribution of both interpersonal meaning and ideational meaning towards teaching English as a foreign language in Indonesia. The result revealed that the prominent use of statements in the text, the author provides a broad and comprehensible information in the short story. Therefore, the objective of the text is successfully achieved based on the text genre. Besides that, the existence of ideational meaning which apply material process as the dominant process revealed that mostly the story emphasizes on what the actor do or what happen to the actor. The employment of material process in narrative text assists the author in designing the story plot in order to construct comprehensible and meaningful story. Keywords: Mood analysis, transitivity, short-story.